Analysis of Transformational Leadership and Compensation on Employee Performance With Work Motivation as a Mediating Variable at the National Plant Seeding and Protection Plantation Medan - Yenni Asmar; Muhammad Isa Indrawan; Husni Muharram Ritonga (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of transformational leadership and compensation on employee performance with work motivation as a mediating variable at the Medan Plantation Seed and Plant Protection Center (BBPPTP). The study used a quantitative method with a survey approach, involving all 135 civil servant employees as samples. Data were collected through questionnaires and analyzed using Partial Least Square (PLS). The results showed that transformational leadership had a positive and significant effect on work motivation, but not a direct significant effect on employee performance. Meanwhile, compensation had a positive and significant effect on both employee performance and work motivation. In addition, work motivation was found to mediate the relationship between transformational leadership and compensation on employee performance. These findings emphasize the importance of developing work motivation through inspirational leadership and fair compensation to achieve optimal employee performance. This study is expected to provide recommendations for BBPPTP Medan in formulating strategies for improving human resources based on competency, motivation, and an effective reward system.